Analisis Faktor-Faktor Yang Mempengaruhi Praktik Pengawas Menelan Obat (PMO) Dalam Pengawasan Penderita Tuberkulosis Paru Di Kota Semarang - Widjanarko, Bagoes; Prabamurti, Priyadi Nugraha; Widyaningsih, Nunuk (Jurnal Promosi Kesehatan Indonesia, 2006)
Background : At least half million a new cases of tuberculosis each year occurred in Indonesia, in which 175.000 of them died. Tuberculosis is the second killer in adults after cardiovascular diseases and the most important killer out of all the communicable diseases. Lung Tuberculosis has been increase every year in Semarang, in order to handle that case, the strategy of DOTS has been used since 2000. In case of that, there are still founded that the number of Drop out to patient is 16%, and the irregular tuberculosis patient is 21%. It happened because the patient didn`t obey to swallow the drugs and the role of PMO was decrease. Knowledge, attitude, and practice of drugs swallowing control (PMO) have a very important role and determine the successful of Pulmonary Tuberculosis Control Programes. This research aim to know factors that having an effect on to exploiting of practice Drugs Swallowing Control (PMO) lung tuberculosis patients in Semarang.Mathod : The type of this research is Explanatory Research that is explaining relation between independent variable and dependent variable through examination of hypothesizing using cross sectional method. Data analysis with Chi-Square statistical test and Logistics Regression. Research population is drugs swallowing control (PMO) of lung tuberculosis patients with positif BTA, counted 254 with 70 people of sample.Result : The result of research show there is a relation between knowledge and attitude (p=0,000), knowledge and practice (p=0,012) , attitude and practice (p=0,001). There is no significant relation between PMO characteristic (age, level of education, work, family status, income, training, duty periode) and PMO practice lung tuberculosis patients.Using Forward Stepwise (Conditional) method the result can be obtained that all independent variable if tested together using logistic regression method yielding one variable show the influence to exploiting of PMO practice : Attitude (p=0,014). The most dominant variable in giving influence to PMO practice is Attitude. One of the variable withgood attitude category hence possibility exploit practice obtained equal 99,93%.Keywords : Lung Tuberculosis, knowledge, attitude, and practice PMO